A novel glycan modifies the flagellar filament proteins of the oral bacterium Treponema denticola. Issue 1 (27th October 2016) - Kurniyati, Kurni; Kelly, John F.; Vinogradov, Evgeny; Robotham, Anna; Tu, Youbing; Wang, Juyu; Liu, Jun; Logan, Susan M.; Li, Chunhao
Summary: While protein glycosylation has been reported in several spirochetes including the syphilis bacterium Treponema pallidum and Lyme disease pathogen Borrelia burgdorferi, the pertinent glycan structures and their roles remain uncharacterized. Herein, a novel glycan with an unusual chemical composition and structure in the oral spirochete Treponema denticola, a keystone pathogen of periodontitis was reported. The identified glycan of mass 450.2 Da is composed of a monoacetylated nonulosonic acid (Non) with a novel extended N7 acyl modification, a 2‐methoxy‐4, 5, 6‐trihydroxy‐hexanoyl residue in which the Non has a pseudaminic acid configuration (L‐ glycero ‐L‐ manno ) and isβ ‐linked to serine or threonine residues. This novel glycan modifies the flagellin proteins (FlaBs) of T. denticola by O ‐linkage at multiple sites near the D1 domain, a highly conserved region of bacterial flagellins that interact with Toll‐like receptor 5. Furthermore, mutagenesis studies demonstrate that the glycosylation plays an essential role in the flagellar assembly and motility of T. denticola . To our knowledge, this novel glycan and its unique modification sites have not been reported previously in any bacteria. Abstract : Swimming with sugar: We demonstrate that the flagellar filament proteins of oral bacterium Treponema denticola are modified with a novel glycan (a C7‐acylated pseudaminic acid derivative, m/z 451.2) and that such a modification is essential for flagellar assembly and motility.